2/1.2 + 2/2.3 + 2/3.4 + ... + 2/2008.2009
Tính:
a)\(\dfrac{1}{n}+\dfrac{1}{n+a}\)với a ;n là số tự nhiên và n khác 0
b) 1/1.2+1/2.3+1/3.4+...+
1/2008.2009
c)3/1.4+3/4.7+3/7.10+...+3/94.97
d)2/1.2+2/2.3+2/3.4+...+
2/2008.2009
Giải:
b) \(\dfrac{1}{1.2}+\dfrac{1}{2.3}+\dfrac{1}{3.4}+...+\dfrac{1}{2008.2009}\)
\(=\dfrac{1}{1}-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{2008}-\dfrac{1}{2009}\)
\(=\dfrac{1}{1}-\dfrac{1}{2009}\)
\(=\dfrac{2008}{2009}\)
c) \(\dfrac{3}{1.4}+\dfrac{3}{4.7}+\dfrac{4}{7.10}+...+\dfrac{3}{94.97}\)
\(=\dfrac{1}{1}-\dfrac{1}{4}+\dfrac{1}{4}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{10}+...+\dfrac{1}{94}-\dfrac{1}{97}\)
\(=\dfrac{1}{1}-\dfrac{1}{97}\)
\(=\dfrac{96}{97}\)
Vậy ...
Các câu sau tương tự
b, \(\dfrac{1}{1.2}+\dfrac{1}{2.3}+\dfrac{1}{3.4}+....+\dfrac{1}{2008.1009}\)
\(=\)\(\dfrac{1}{1}-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+....+\dfrac{1}{2008}-\dfrac{1}{2009}\)
\(=\dfrac{1}{1}-\dfrac{1}{2009}=\dfrac{2009}{2009}-\dfrac{1}{2009}=\dfrac{2008}{2009}\)
c,\(\dfrac{3}{1.4}+\dfrac{3}{4.7}+\dfrac{3}{7.10}+....+\dfrac{3}{94.97}\)
\(=\dfrac{4-1}{1.4}+\dfrac{7-4}{4.7}+\dfrac{10-7}{7.10}+....+\dfrac{97-94}{94.97}\)
\(=\dfrac{4}{1.4}-\dfrac{1}{1.4}+\dfrac{7}{4.7}-\dfrac{4}{4.7}+\dfrac{10}{7.10}-\dfrac{7}{7.10}+...+\dfrac{97}{94.97}-\dfrac{94}{94.97}\)
\(=\dfrac{1}{1}-\dfrac{1}{4}+\dfrac{1}{4}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{10}+....+\dfrac{1}{94}-\dfrac{1}{97}\)
\(=\dfrac{1}{1}-\dfrac{1}{97}=\dfrac{97}{97}-\dfrac{1}{97}=\dfrac{96}{97}\)
tinh tong : \(\dfrac{2}{1.2}\) + \(\dfrac{2}{2.3}\) + \(\dfrac{2}{3.4}\) +.............+\(\dfrac{2}{2008.2009}\)
\(\dfrac{2}{1.2}+\dfrac{2}{2.3}+\dfrac{2}{3.4}+...............+\dfrac{2}{2008.2009}\)
\(=2\left(\dfrac{1}{1.2}+\dfrac{1}{2.3}+\dfrac{1}{3.4}+................+\dfrac{1}{2008.2009}\right)\)
\(=2\left(1-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+.................+\dfrac{1}{2008}-\dfrac{1}{2009}\right)\)
\(=2\left(1-\dfrac{1}{2009}\right)\)
\(=2.\dfrac{2008}{2009}=\dfrac{4016}{2009}\)
Tính tổng: 1.2+2.3+3.4+4.5+...+2008.2009
Ta có : 1.2 + 2.3 + 3.4 + ... + 2008.2009
= ( 1.2.3 + 2.3.3 + 3.4.3 + ... + 2008.2009.3 ) :3
= [ 1.2.3 + 2.3.( 4 - 1 ) + 3.4.( 5 - 2 ) + ... + 2008.2009.( 2010 - 2007 )] : 3
= [ 1.2.3 + 2.3.4 - 2.3.1 + 2.4.5 - 3.4.2 + ... + 2008.2009.2010 - 2008.2009.2007 ] : 3
= ( 2008.2009.2010 ) :3
= 2702828240
Tính tổng: 1.2+2.3+3.4+4.5+...+2008.2009
1.2 + 2.3 + 3.4 + 4.5 +...+ 2008.2009
= \(\frac{1}{3}\left(1.2.3+2.3.3+3.4.3+4.5.3+...+2008.2009.3\right)\)
= \(\frac{1}{3}\left(1.2.3+2.3.\left(4-1\right)+3.4.\left(5-2\right)+4.5.\left(6-3\right)+...+2008.2009.\left(2010-2007\right)\right)\)
\(=\frac{1}{3}.2008.2009.2010=670.2008.2009\) số lớn nên bạn tự tính tiếp nhé!
tính
1.2+2.3+3.4+4.5+5.6+...+2008.2009
Đặt A = 1.2 + 2.3 + 3.4 + ..... + 2008.2009
<=> 3A = 1.2.3 + 2.3.3 + 3.4.3 + .... + 2008.2009.3
<=> 3A = 1.2.3 + 2.3.( 4 - 1 ) + 3.4.( 5 - 2 ) + ...... + 2008.2009.( 2010 - 2007 )
<=> 3A = 1.2.3 + 2.3.4 - 1.2.3 + 3.4.5 - 2.3.4 + .... + 2008.2009.2010 - 2007.2008.2009
<=> 3A = 2008.2009.2010
=> A = ( 2008.2009.2010 ) : 3
tính nhanh A=2009/1.2+2009/2.3+2009/3.4+.............+2009/2008.2009
Tính nhanh:
A = 2009/1.2 + 2009/2.3 + 2009/3.4 + ... + 2009/2008.2009
a=2009(1-1/2+1/2-1/3+1/3-1/4+1/4-1/5+.........+1/2008-1/2009)
=2009x2008/2009
=2008
Tính bằng cách hợp lí (nếu có thể) \(\frac{1^2}{1.2}\).\(\frac{2^2}{2.3}.\frac{3^2}{3.4}.\frac{4^2}{4.5}...\frac{2008^2}{2008.2009}\)
2/1.2 + 2/2.3 +2/3.4+..........+2/99.100
= 2/1 - 2/2 + 2/2 - 2/3 + 2/3 - 2/4 + ..... + 2/99 - 2/100
= 2/1 + 2/100
= 101/50
2/1 - 2/2 + 2/2 - 2/3 + 2/3 - 2/4 +...+ 2/99 - 2/100
= 2/1 - 2/100
= 99/50